Persistent Organic Pollutants’ Threats and Impacts on Food Safety in the Polar Regions—A Concise Review - Dele Raheem; Marco Trovò; Constanza Carmona Mora; Clara Vassent (Pollutants)
The threats posed by Persistent Organic Pollutants (POPs) impact food safety and, by implication, food security in the polar regions. POPs tend to persist in the environment and the fatty tissues of animals, thereby constituting long-term contamination. Due to the cold climate and geography of these polar regions, they create a sink for these pollutants, which travel from their source of production and accumulate in food chains, resulting in health risks to the ecosystem, animals, and humans of the Arctic and Antarctica. In this paper, we draw attention to the threats posed by POPs and how they can lead to food insecurity, negatively affecting health due to unsafe traditional foods. A narrative synthesis methodology was employed, systematically analyzing historical data, activities, and research trends on POP contamination in polar ecosystems. We also highlight resilience promoted by Arctic governance, with a focus on how the issues of POPs became an international matter from the 1970s, with three United Nations (UN) conventions: the UN-Environment Stockholm Convention on Persistent Organic Pollutants, the UN Minamata Convention on mercury, and the UN-ECE Convention on Long-range Transboundary Air Pollution. These conventions led to the start of several monitoring activities in the polar regions, transforming the POPs into a global topic. We also consider the intertwined effect of climate change on POPs. Additionally, the human rights paradigm in relation to food security and sovereignty for polar communities is explored. Strengthening the resilience of communities in the polar regions requires recognition of these nutritious traditional foods as an aspect of cultural identity that must be safe and easily accessible. We focus on developments, improvements, the role of international cooperation, and frameworks to assist in research and regulations. Furthermore, establishing systems that engage local communities to consistently monitor POPs regularly will lead to a better understanding of these threats. Ultimately, this narrative provides a look into the past and current research of POPs and their monitoring in the polar regions.